Food Crisis in Yemen: The Roles of Food and Agriculture Organization (FAO) from 2015 to 2020 - Sihaloho, Rezya Agnesica Helena; Prabowo, Tri Bagus; Kusuma, Roby Panji (Nation State: Journal of International Studies, 2022)
Since the Yemen conflict in 2015, the food crisis and water scarcity in Yemen have been getting worse and increasing the number of victims who died due to hunger and malnutrition. Therefore, Yemen food insecurity also ultimately has an impact on politics, the economy, and various other aspects. Thus, the international community tried to prevent worse situations through international cooperation. Food and Agriculture Organization (FAO) carried out this cooperation with the commitment of its member countries to solve this issue. Therefore, that is the beginning of this research which discusses FAO's efforts in dealing with the food crisis in Yemen. This paper uses the theory of neoliberal institutionalism with qualitative research methods to get a full illustration of FAO's activities through a literature review. Finally, this paper finds out that FAO has contributed and played an important role in dealing with the Yemen food crisis through program that have been designed and implemented.